2014
DOI: 10.1016/j.ijid.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparable efficacy of tenofovir versus entecavir and predictors of response in treatment-naïve patients with chronic hepatitis B: a multicenter real-life study

Abstract: The two drugs appear to have similar efficacy in CHB patients. However, 7% of patients on ETV therapy had virological breakthrough, while none of the patients on TDF therapy did.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0
15

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 28 publications
6
32
0
15
Order By: Relevance
“…[5] At present, there are many clinical studies of multicenter, large-scale samples of TDF here and abroad. [67891011121314] Among them, TDF in vitro experiments showed that it had a strong antiviral capacity against both hepatotropic viruses and retroviruses, and it can inhibit the activity of HBV DNA polymerase, which had a good inhibitory effect on HBV DNA replication in wild-type HBV. In vitro studies of TDF treatment for HBV infection with lamivudine (LAM) and adefovir dipivoxil (ADV) resistance also showed that TDF has a good inhibitory effect on viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…[5] At present, there are many clinical studies of multicenter, large-scale samples of TDF here and abroad. [67891011121314] Among them, TDF in vitro experiments showed that it had a strong antiviral capacity against both hepatotropic viruses and retroviruses, and it can inhibit the activity of HBV DNA polymerase, which had a good inhibitory effect on HBV DNA replication in wild-type HBV. In vitro studies of TDF treatment for HBV infection with lamivudine (LAM) and adefovir dipivoxil (ADV) resistance also showed that TDF has a good inhibitory effect on viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…The use of tenofovir and entecavir was compared in 13 studies with average sample sizes of 62 per treatment group (range, 22‐148). The first RCT of HBV‐infected adults with decompensated cirrhosis showed no significant difference in serum creatinine or creatinine clearance over 48 weeks of tenofovir (n = 45) or entecavir (n = 22) . The second RCT of 200 HBV‐infected adults (100 on tenofovir, 100 on entecavir) showed no significant decline in renal function and no difference in adverse events .…”
Section: Renal and Bone Disease In Persons On Na Therapymentioning
confidence: 99%
“…Previous studies have described rates of virological breakthrough ranging between 0% and 55.8% [11,[18][19][20][21], with lower rates reported in patients receiving second generation medications such as entecavir (ETV) and tenofovir (TDF) [21]. Hongthanakorn et al (2011) were the first to highlight that non-adherence to HBV antiviral medications posed a problem [11].…”
Section: Virological Breakthrough Is Defined By the American Associatmentioning
confidence: 99%